2023
DOI: 10.1111/corg.12509
|View full text |Cite
|
Sign up to set email alerts
|

An axe to grind: Family outsiders and firms doing good

Abstract: Research Question/IssueThis paper examines the relationship between having nonfamily members (i.e., family outsiders) as board chairs and corporate philanthropy.Research Findings/InsightsIn a hand‐collected dataset of Chinese family firms, we find that firms invest less in philanthropy when the board chair is a nonfamily member. However, this impact is mitigated when the chair's discretion is restricted, as in highly visible firms or firms controlled by the founding family. The negative relation between nonfam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Giannarakis et al (2022) investigated the impact of eight corporate governance attributes on social aspects of CSR and revealed the high significance of female directors, board positions and the CSR committee on social performance. Similarly, a study by Jiang et al (2023) observed high levels of negligence from non-family board members towards firms' social actions or philanthropy. See Table 2 for further details.…”
Section: Introduction To Csp Driversmentioning
confidence: 92%
See 4 more Smart Citations
“…Giannarakis et al (2022) investigated the impact of eight corporate governance attributes on social aspects of CSR and revealed the high significance of female directors, board positions and the CSR committee on social performance. Similarly, a study by Jiang et al (2023) observed high levels of negligence from non-family board members towards firms' social actions or philanthropy. See Table 2 for further details.…”
Section: Introduction To Csp Driversmentioning
confidence: 92%
“…There are an abundance of research papers discussing various aspects of the CSP framework (Wood, 2010; Beisland et al ., 2021; Jiang et al ., 2023). Among the first few researchers, Wood (1991) in his review paper explained various roles of CSP and stakeholders while analyzing social actions of a firm.…”
Section: Review Of Literature Involving Cspmentioning
confidence: 99%
See 3 more Smart Citations